The Phenomenon of Spiritual Habitat in the Yakut Heroic Epic - Savvinov, Andrey Savvich; Sleptsova, Galina Grigorievna (Journal of History Culture and Art Research, 2018)
In the Yakut heroic epic olonkho (“Nyurgun Bootur the Swift” by Platon A. Oyunsky, Elbet Bergen of N.T. Abramova), the main person is the hero of aiyy. He is called to protect his people and tribe. He is the guarantor of the “future life of the genus “Aiyy aimaga”, i.e. the tribe of divine origin, therefore, in accordance with its high purpose, the hero is portrayed as strong and majestic. He is opposed by the hero of the tribe “Abaasy aimaga” - literally a representative of the devil’s tribe, who attacks people and abducts the beautiful bride, the future mother of the successor of the genus of Aiyy aimaga. The last circumstance in the world of the olonkho is a symbol of an assassination attempt on the bright future of people. Therefore, the hero of aiyy at the end defeats the hero of the tribe of “abaasy aimaga”. But not everything is so simple. In the single combat of the hero of the tribe of “aiyy aimaga” and the hero of the “abaasy aimaga”, the first hero does not always win. And the cause of the defeat is reduced not only to the sentences sent by higher forces for too arrogant attitude towards people of the Aiyy Aimaga family, the Higher Powers. This article is devoted to understanding the image of the hero “Ogo Tulayakh” (“Child-orphan”) from the genus of Aiyy aimaga. The authors set the task to show the spiritual, moral, emotional, intellectual potential of the olonkho “Nyurgun Bootur the Swift”, which is necessary to overcome the spiritual orphanhood of the individual. If a person does not know love, does not know the natural laws, the commandments of people’s lives and therefore does not follow them, he considers himself to be abandoned and lonely. This is the manifestation of spiritual orphanhood. As a methodological principle of work, the olonkho is considered as the basic matrix in the spiritual development of a nation. The novelty of the research is that the authors disclose through the images of the heroes of this olonkho the ways to overcome spiritual orphanhood. The practical significance of the research is that the philosophical conception of the development of value orientations of the Sakha ethnofor has been developed, it tried and tested basic components – the theoretical model, mechanisms, authoring methods, constitute the scientific basis for the development and preservation of ethno-value orientations, making optimal decisions on the acute problems of the cultural, spiritual, political coexistence and dynamic development of the representative of the Sakha ethnos.